Решите уравнение
nа)(3х+4)+(2х+3)=-7х+12
nб)8-(15-11х)=(5х+3)-(-7х+4)
nв)((3+4х)-(11+10х)=7+(13-4х)
nг)5(3х-2)=3(х+1)-2•(х+2)
nПомогите пожалуйста ответ с решением
Ответ
5/5 (1 оценка)
1
tatsach 2 года назад
Светило науки - 926 ответов - 54483 помощи

Ответ:


Пошаговое объяснение:

а)(3х+4)+(2х+3)=-7х+12

3х+2х+7х=12-3-4

12х=5

Х=5:12

Х=5/12


б)8-(15-11х)=(5х+3)-(-7х+4)

8-15+11х=5х+3+7х-4

11х-5х-7х=3-4+15-8

-х=6

Х=-6


в)((3+4х)-(11+10х)=7+(13-4х)

3+4х-11-10х=7+13-4х

4х-10х+4х=7+13+11-3

-2х=28

Х=28:(-2)

Х=-14


г)5(3х-2)=3(х+1)-2•(х+2)

15х-10=3х+3-2х-4

15х-3х+2х=3-4+10

14х=9

Х=9:14

Х=9/14